Inactivation of the pre-mRNA cleavage and polyadenylation factor Pfs2 in fission yeast causes lethal cell cycle defects. - Wang, S; Asakawa, K; Win, T; Toda, T; Norbury, C (2005)
Faithful chromosome segregation is fundamentally important for the maintenance of genome integrity and ploidy. By isolating conditional mutants defective in chromosome segregation in the fission yeast Schizosaccharomyces pombe, we identified a role for the essential gene pfs2 in chromosome dynamics. In the absence of functional Pfs2, chromosomal attachment to the mitotic spindle was defective, with consequent chromosome missegregation. Under these circumstances, multiple intracellular foci of spindle checkpoint proteins Bub1 and Mad2 were seen, and deletion of bub1 exacerbated the mitotic defects and the loss of cell viability that resulted from the loss of pfs2 function. Progression from G1 into S phase following release from nitrogen starvation also required pfs2+ function. The product of the orthologous Saccharomyces cerevisiae gene PFS2 is a component of a multiprotein complex required for 3'-end cleavage and polyadenylation of pre-mRNAs and, in keeping with the conservation of this essential function, an S. pombe pfs2 mutant was defective in mRNA 3'-end processing. Mutations in pfs2 were suppressed by overexpression of the putative mRNA 3'-end cleavage factor Cft1. These data suggest unexpected links between mRNA 3'-end processing and chromosome replication and segregation.